2019
DOI: 10.1371/journal.pone.0224516
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood crime, disorder and substance use in the Caribbean context: Jamaica National Drug Use Prevalence Survey 2016

Abstract: The purpose of the study was to examine the role of objective and subjective measures of neighborhood crime and disorder on substance use among a nationally representative sample of 4525 Jamaicans aged 12–65 years. Log-Poisson models with generalized estimating equations were used to estimate relative risks (RR) and 95% confidence intervals (CI). A test of interaction was used to determine presence of effect modification by sex. Approximately 39% of the study population reported past-month alcohol use; 10% pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…MAUP arises from aggregating point-based measures of spatial phenomena to arbitrarily defined geographic areas and the use of administrative boundaries as a proxy for neighborhood. Although EDs are the smallest unit of aggregation in Jamaica to facilitate the collection of census and survey data, they provide only a rough measure of neighborhood context [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAUP arises from aggregating point-based measures of spatial phenomena to arbitrarily defined geographic areas and the use of administrative boundaries as a proxy for neighborhood. Although EDs are the smallest unit of aggregation in Jamaica to facilitate the collection of census and survey data, they provide only a rough measure of neighborhood context [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies were identified, one reporting an association between neighbourhood crime and childhood malnutrition (Thompson et al, 2017) and the other reporting associations between perceived neighbourhood characteristics and depressive symptoms among adolescents in Jamaica and other Caribbean islands (Lowe et al, 2014). More recently, associations have been reported between neighbourhood disorder and cumulative biological risk and substance use (Cunningham-Myrie et al, 2018;Felker-Kantor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies covering districts, boroughs, and municipalities often show no associations between smoking and socio-economic characteristics, for example, the crime rate ( 20 ), the unemployment rate ( 22 ), the average per capita income ( 22 , 23 ), or the Gini index ( 23 ). Furthermore, a number of studies, surprisingly, show positive associations between socio-economic characteristics and smoking, which means that an improvement of the socio-economic situation caused an increase in the degree of smoking incidence ( 14 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is significant that the impact of territorial living conditions on individual health indicators can vary considerably depending on the scale of the selected territory (16)(17)(18)(19). Most of the "smoking geography" studies focus on small territorial entities: Postal index zones, city districts, municipalities, and areas with a population of under 50,000-100,000 people (14,15,(20)(21)(22)(23)(24)(25)(26)(27). There are considerably fewer works devoted to the research of territorial smoking predictors at the international level (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation